2019
DOI: 10.1590/1413-82712019240307
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Greed Scale: evidências de sua estrutura interna e parâmetros dos itens

Abstract: Resumo Este estudo objetivou conhecer as evidências da estrutura interna da Dispositional Greed Scale (DGS) e os parâmetros de seus itens. Contou-se com a participação de 338 pessoas com média de idade de 26,5 anos (DP = 8,18), que responderam a DGS e perguntas demográficas. Os resultados indicaram uma solução unifatorial da DGS (Ω = 0,75). Análises via Teoria de Resposta ao Item demonstraram que os itens da DGS discriminam adequadamente os participantes e exigem baixa a moderada quantidade de traço latente pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Study 2–5 (total N = 1,496) found that the DGS was distinct from materialism, and predicted greedy behavior in dictator, ultimatum, and public good games. Several of these findings were replicated with a Japanese (Masui et al, 2018), a Brazilian Portuguese (Alves Freires et al, 2019), a Chinese (Liu, Sun, Ding, et al, 2019), and a Russian adaptation of the DGS (Shirko & Furmanov, 2020). In other research, the DGS predicted the financial behavior of adolescents (Seuntjens et al, 2016), a variety of immoral attitudes and behaviors (Seuntjens et al, 2019), working and earning in the laboratory (Zeelenberg et al, 2020), benign and malicious envy (Crusius et al, 2021), but not individual trading behavior in experimental asset markets (Hoyer et al, 2021).…”
mentioning
confidence: 84%
“…Study 2–5 (total N = 1,496) found that the DGS was distinct from materialism, and predicted greedy behavior in dictator, ultimatum, and public good games. Several of these findings were replicated with a Japanese (Masui et al, 2018), a Brazilian Portuguese (Alves Freires et al, 2019), a Chinese (Liu, Sun, Ding, et al, 2019), and a Russian adaptation of the DGS (Shirko & Furmanov, 2020). In other research, the DGS predicted the financial behavior of adolescents (Seuntjens et al, 2016), a variety of immoral attitudes and behaviors (Seuntjens et al, 2019), working and earning in the laboratory (Zeelenberg et al, 2020), benign and malicious envy (Crusius et al, 2021), but not individual trading behavior in experimental asset markets (Hoyer et al, 2021).…”
mentioning
confidence: 84%
“…Participants were 305 college students (140 women; M age = 19.87, SD = 2.15) from a Colombian Business School. We based the sample size on those of related papers presenting a translation and validation of the Dispositional Greed Scale languages (Japanese: Masui et al, 2018, N = 856; Mandarin Chinese: Liu et al, 2019; Sample A, N = 133, Sample B, N = 303; Brazilian Portuguese: Freires et al, 2019, N = 338; Russian: Poluektova et al, 2022, N = 350). The sample size is well above 250 that Schönbrodt and Perugini (2013) give as a benchmark for achieving stable correlations.…”
Section: Methodsmentioning
confidence: 99%
“…The scale is unidimensional, with excellent reliabilities, construct and discriminant validity, and temporal stability (see, for example, Seuntjens, Zeelenberg, Van De Ven, & Breugelmans, 2015; Zeelenberg et al, 2020, 2022). The DGS has been applied with a wide range of groups, such as adolescents, university students, people living in low SES circumstances, and representative samples of the general (working) population (e.g., Freires et al, 2019; Liu et al, 2019; Masui et al, 2018; Poluektova et al, 2022; Seuntjens, Zeelenberg, Van de Ven & Breugelmans, 2015; Van Muijen & Melse, 2015; Zeelenberg et al, 2020, 2022). Hence, we expect the DGS-Spanish to show a unidimensional structure with good item-total correlations and reliability.…”
Section: The Dispositional Greed Scale (Dgs)mentioning
confidence: 99%
“…Há poucos esforços empíricos em psicologia abordando o referido construto (Gilliland & Anderson, 2014), sobretudo no que tange à operacionalização das diferenças individuais na ganância, até recentemente inexistente nos cenários internacional (Krekels & Pandelaere, 2015) e nacional (Freires et al, 2019). Estudos sobre a ganância acentuavam mais uma perspectiva puramente situacional (e.g., injustiça distributiva e atribuição de responsabilidade: a noção de ganância percebida; quando as pessoas são vistas como tendo mais do que precisam, produzem um cenário de baixa cooperação e alta competição; Gilliland & Anderson, 2011), sem enfatizar a possibilidade do entendimento do que causa comportamentos gananciosos de sujeitos em certas situações, enquanto em outras não (Krekels & Pandelaere, 2015).…”
Section: O Construto Da Ganânciaunclassified